Implementasi Metode Enhanced Audio Steganogafi (EAS) Untuk Penyembunyian Text Terenkripsi Algoritma Gost - Selamat G M Siregar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Audio files in the Mp3 format are used as cover media. To be able to insert a secret message into the container media requires a method that can modify the object into a new object with confidential information in it without any noticeable changes from the initial object. The method used in this study is the EAS (Enhanced Audio Steganography) method and to encrypt the message using the GOST algorithm. EAS (Enhanced Audio Steganography) which is a method for inserting an encrypted message first to strengthen a secret message and then inserting it into an audio file. Encryption is done on the message using the GOST algorithm. The GOST method is a block cipher algorithm developed by a Soviet national. GOST is an abbreviation of "Gosudarstvennyi Standard" or "Government Standard". This algorithm is a simple encryption algorithm that has 32 rounds of processes and uses 64 bit block cipher with 256 bit keys. The GOST method also uses 8 different S-Boxes and XOR and Left Circular Shift operations. However, modifying audio file bits sequentially can create huge noise and invite suspicion for others that there is a message embedded in it. The method that is able to reduce the occurrence of noise in audio files after inserting a message is the EAS (Enhanced Audio Steganography) method. The EAS method is a modification of the LSB method. Where in the EAS method, the bytes that are used as containers only selective bytes, that is, the insertion of bits in the storage media is only done in blocks that are 254 or 255 bytes only, so that the storage media will not experience significant damage. The first input message format *. Doc or *. Pdf, will be encrypted using the Gost algorithm, the encryption process begins with input plaintext and key. After the message is encrypted then the embedding process uses the EAS method. Input audio file that will be used as a container, after that the encrypted file will be inserted in the audio file. In the embedding process, a large number of locations are available on the audio file. Audio files that are used as storage media must have a number of bytes worth 254 or 255 which are sufficient to hold the message file.